Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.4049/jimmunol.166.6.4154
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Expression of a Functional Receptor for the C5a Complement Activation Fragment

Abstract: The present studies were undertaken to determine whether neuronal subsets in normal brains constitutively express functionally competent C5a receptors. In situ hybridization studies coupled with immunohistochemical approaches revealed that most neurons in the hippocampal formation, many pyramidal cortical neurons, and cerebellar Purkinje neurons in normal human and murine brains constitutively express C5a receptors. Neuronal C5a receptors bound C5a-coated fluorescent microspheres, and primary rodent hippocampa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
102
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 59 publications
4
102
1
Order By: Relevance
“…In situ hybridization and immunohistochemistry analysis also revealed a constitutive expression of mouse and rat C3aR in cortical and hippocampal neurons (17,19) as well as in cerebellar Purkinje cells (19). Controversial results have been published for C5aR, which was first hardly detected by in situ hybridization or immunohistochemistry in neurons from rodent adult brains (18,22) but was recently identified on mouse pyramidal neurons in hippocampus and neocortex as well as on Purkinje cells in cerebellum (26). C5aR expression seemed induced by inflammatory stimuli (18,22) and is found in cultured murine corticohippocampal neurons (21,28) and neuroblastoma cells (24 -26).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In situ hybridization and immunohistochemistry analysis also revealed a constitutive expression of mouse and rat C3aR in cortical and hippocampal neurons (17,19) as well as in cerebellar Purkinje cells (19). Controversial results have been published for C5aR, which was first hardly detected by in situ hybridization or immunohistochemistry in neurons from rodent adult brains (18,22) but was recently identified on mouse pyramidal neurons in hippocampus and neocortex as well as on Purkinje cells in cerebellum (26). C5aR expression seemed induced by inflammatory stimuli (18,22) and is found in cultured murine corticohippocampal neurons (21,28) and neuroblastoma cells (24 -26).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, it has been reported that C5a mediates apoptosis in neuroblastoma cells (24,25). In contrast, C5a protects differentiated human neuroblastoma cells from the neurotoxic effect of the amyloid A␤ peptide (26), and a possible neuroprotective role for C5a has been suggested in Alzheimer's disease (27). Moreover, C5-deficient mice are more sensitive to kainic acid excitotoxicity (28), and C5a has been found to protect neurons from apoptotic cell death in vitro and in vivo in a model of intracerebroventricular kainic injection in mice (21).…”
mentioning
confidence: 99%
“…In the search for evidence of C5aR in neurons, researchers discovered that C5a promotes proliferation of undifferentiated human neuroblastoma cells (44). The proliferative effects of C5a/C5aR binding seem to be partially mediated by protein kinase C and NF-κB activation (44). Complement-mediated tumor proliferation has also been observed in the TC-1 syngeneic model of murine cervical cancer (11).…”
Section: Complement Promotes Oncogenesismentioning
confidence: 99%
“…Intriguingly, two studies have shown direct complementmediated neoplastic proliferation. In the search for evidence of C5aR in neurons, researchers discovered that C5a promotes proliferation of undifferentiated human neuroblastoma cells (44). The proliferative effects of C5a/C5aR binding seem to be partially mediated by protein kinase C and NF-κB activation (44).…”
Section: Complement Promotes Oncogenesismentioning
confidence: 99%
“…Although initially described as leukocyte chemoattractants and anaphylatoxins, it is now clear that C5a and C3a are involved in microbial host defense, immune regulation (1), and protection against toxic insult (2)(3)(4)(5). C5a and C3a are also reported to have psychopharmacological effects on feeding and drinking behavior (6,7).…”
mentioning
confidence: 99%